Solid State Fermentation of Maize (Zea mays) Offal by Rhizopus oligosporus under Acidic and Basic Conditions - Anigboro, A. A.; Aganbi, E.; Tonukari, N. J. (Journal of Scientific Research, 2020)
Maize offal, a by-product of maize milling industry that constitutes environmental pollution is under-utilized. This study investigated the effect of solid state fermentation on maize offal using Rhizopus oligosporus under acidic and basic conditions (pH range of 3 to 9). Soluble proteins content, glucose and amylase activity of the fermented by-products were evaluated after five days’ period of fermentation. The result showed a significant increase in soluble proteins content at pH 3, glucose at pH 6 and amylase activity at pH 7 when compared with the control (P < 0.05). This showed that solid state fermentation improves the nutritional value of maize offal at different pH values. Thus, livestock feeds formulation industries could harness this process in the utilization of maize offal for poultry, other farm animal feeds and food fortification for protein enhancement thereby, preventing environmental pollution.